Analysis of the copolymer composition based on the simulation of small reaction systems - Lechowicz, Jaromir (Polimery, 2022)
The course of gradient copolymerization of bifunctional monomers was investigated using the Monte Carlo simulation method. The copolymer composition was determined by averaging the composition of successive segments of macromolecular chains. Changing the size of the segments made it possible to estimate the gradient profile of the composition of small reaction systems. The applied procedure does not require a large computing system.